Caracterização da qualidade de frutos de diferentes acessos de umbuzeiro no cariri ocidental paraibano. - Saraiva, Maria Monique Tavares (2020)
The umbu tree (Spondias tuberosa Arr. Câm.) is the main perennial native and endemic fruit species in the Brazilian semiarid region. It has great environmental and socioeconomic importance for the rural populations of the region, mainly due to the extraction of fruits with high nutritional value. In this context, it aimed to georeference and characterize different accessions of umbu located in Serra do Jatobá, municipality of Serra Branca - PB, through physical, physical-chemical and chemical aspects. This research addresses two chapters: General considerations and characterization and variability of umbu in Serra do Jatobá, Western Cariri of Paraíba. 14 accessions were studied, in which initially they were selected and georeferenced, and then evaluated through the mass, percentage of peel, seed and pulp; yield, length, width, shape, firmness, colorimetric analysis, titratable acidity, pH, soluble solids, soluble solids / titratable acidity ratio, vitamin C, sugars, moisture and ash. With submission to the mean test, linear correlation and grouping. All of them differed statistically, and there was high variability in shape, colors, size and chemical composition. The fruits of accessions 4, 8 and 13 stood out due to the significant mass and dimensions; all treatments showed a yield above 84%, with emphasis on access 7 with 92.82%; and as for the physicochemical characteristics, access 1 have the highest vitamin C content, 7 have the highest amount of soluble solids and 11 have the highest soluble solids / titratable acidity ratio. The cluster analysis showed two groups, in which access 1 was more different from the others and accesses 2 and 6 had the greatest similarity. In general, through the variability of the attributes studied, it can be said that the fruits have potential that make them possible for different applications, according to the requirements of the industry and consumed.